Current treatments in diabetic macular oedema: systematic review and meta-analysis. Issue 3 (1st March 2013) - Ford, John Alexander; Lois, Noemi; Royle, Pamela; Clar, Christine; Shyangdan, Deepson; Waugh, Norman
Abstract : Objectives: The aim of this systematic review is to appraise the evidence for the use of anti-VEGF drugs and steroids in diabetic macular oedema (DMO) as assessed by change in best corrected visual acuity (BCVA), central macular thickness and adverse events Data source: MEDLINE, EMBASE, Web of Science with Conference Proceedings and the Cochrane Library (inception to July 2012). Certain conference abstracts and drug regulatory web sites were also searched. Study eligibility criteria, participants and interventions: Randomised controlled trials were used to assess clinical effectiveness and observational trials were used for safety. Trials which assessed triamcinolone, dexamethasone, fluocinolone, bevacizumab, ranibizumab, pegaptanib or aflibercept in patients with DMO were included. Study appraisal and synthesis methods: Risk of bias was assessed using the Cochrane risk of bias tool. Study results are narratively described and, where appropriate, data were pooled using random effects meta-analysis. Results: Anti-VEGF drugs are effective compared to both laser and placebo and seem to be more effective than steroids in improving BCVA. They have been shown to be safe in the short term but require frequent injections. Studies assessing steroids (triamcinolone, dexamethasone and fluocinolone) have reported mixed results when compared with laser or placebo. Steroids have been associated with increased incidence of cataracts and intraocular pressure rise but require fewer injections, especially when steroid implants are used. Limitations: The quality of included studies varied considerably. Five of 14 meta-analyses had moderate or high statistical heterogeneity. Conclusions and implications of key findings: The anti-VEGFs ranibizumab and bevacizumab have consistently shown good clinical effectiveness without major unwanted side effects. Steroid results have been mixed and are usually associated with cataract formation and intraocular pressure increase. Despite the current wider spectrum of treatments for DMO, only a small proportion of patients recover good vision (≥20/40), and thus the search for new therapies needs to continue.